PENGARUH MEDIA PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP PRESTASI BELAJAR (Studi Eksperimen Pada Mata Pelajaran Kimia SiswaKelas XTO SMK Negeri 4 Kota Bengkulu) - Selvi Selvi; Wachidi Wachidi (DIADIK, 2020)
This research was aimed to discover the influence of the learning media (multimedia and  real)  and  cognitive  style  (field  independent  and  field  dependent)  toward  the learning achievement. The population of this research was the students of XTO of SMKN 4 Bengkulu City for academic year of 2019/2020 on the five parallel grade of 162 students. The sample was taken by probability sampling technique. This research was conducted to 33 students of XTO3 as the experiment class which was using the media of multimedia learning and to the other 33 students of XTO4 as the control class which was using realia learning media. The design used in this research was factorial design (2 x 2) in which the data was analyzed by using the two-way ANOVA and t-Test variance.  The  results  showed  that:  (1)  the  students  with  learning  multimedia achievement were higher than them who were using the real learning media; (2) the students with the independent field cognitive style achievement were higher than them who have the dependent cognitive style; (3) there was an interaction between the use of learning media and the cognitive style to the learning achievement.